Microstructure and corrosion resistance of laser cladding and friction stir processing hybrid modification Al-Si coatings on AZ31B. (November 2016) - Liu, Fenjun; Ji, Yan; Meng, Qingsen; Li, Zengsheng
Abstract: Al-Si coatings were prepared on AZ31B magnesium alloy by laser cladding (LC), friction stir processing (FSP) and hybrid technology (LC-FSP). The coating microstructure, composition and corrosion resistance were investigated using scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD) and electrochemical measurement. The results indicated that compact, uniform, crack and porous free coatings, which metallurgically bonded to the AZ31B magnesium alloy substrate, were achieved compared with LC coatings. The coatings mainly consisted of Mg2 Si, Al12 Mg17 and AlMg phases. The coatings contained multiplicate Mg intermetallic compounds exhibited better corrosion resistance as compared with the untreated AZ31B. The formation of compact and uniform Mg intermetallic compounds in the coatings remarkably improved corrosion resistance as compared with LC coatings. Highlights: Al-Si coatings were successfully prepared using laser cladding and FSP hybrid technology. The microstructures of LC coatings were evolved into more compact and uniform after FSP. The coatings exhibited well metallurgical bonding and excellent corrosion resistance. The corrosion resistance of coatings prepared by FSP preceded both laser cladding and substrate.